Contribution of community development projects towards poverty alleviation in Thulamela Local Municipality, Limpopo Province - Malovha, Shandukani Shedwin (University of Limpopo, 2013)
The research study investigated the contribution of community development projects towards poverty alleviation in Thulamela Local Municipality of Limpopo province. This research study seeks to investigate the factors that hinder community development projects from contributing positively towards the improvement of the lives of rural communities in the area of the study. This study is also concerned with the development of effective strategies that will enhance the capacity of community development project managers and change their perception and that of other stakeholders with regard to the implementation of community development projects. The literature review established the relationship between community development project and project management. In this regard, the study showed that community projects run by project managers with proper knowledge of and skills in project management impact positively on the improvement of the lives of the rural communities. In this study, a mixed research design approach was used in the investigation of the factors that hinder community projects to contribute positively towards poverty alleviation in Thulamela Local Municipality. Questionnaires and structured interviews were used to collect data from the target population. The findings of the study suggest that most managers of the community development projects lack training in project management.They also revealed that there were inadequate resources; there is a lack of community participation in decision-making, and shortage of funds hampered the sustainability of community development projects. To conclude, it is expected that the recommendations of this research study will highlight the strategies that could be put in place to improve the management of community development projects in order to improve the livelihoods of people in the Thulamela Local Municipality.
Thesis (M.Dev.) --University of Limpopo, 2013
Keywords: Community development; Poverty alleviation projects; Thulamela Local Municipality; Community development -- South Africa; Rural development; Economic development projects -- Developing countries